Anthropometric Study of Nasal Index Among the Youth of Madheshis Community of Nepal - Surendra, Kumar Sah; Man, Kumar Tamang; Deepak, Chaudhary; Amit, Kumar Shah (International Journal of Human Anatomy, 2021)
Introduction The nose is one of the important component of the face which is considered as the major clue for the ethnic origin. The proportion of the nose is determined on the same principal as that of the skull.The external nose extends the nasal cavities onto the front of the face and positions the nares so that they point downwards. The shape of the nose is pyramidal with its apex anterior in position. The upper angle of the nose between the openings of the orbits is continuous with the forehead. Materials and Methods This study was carried out among residents of Ramnagar Gaupalika-7, Sarlahi,Nepal, one of the core region of Madhesh Nepal dated Jan 2021 to April 2021.The cohort consists of independent adults of age group 17-45 and consenting adults from the metropolis. Ethical approval was sought prior to conducting the study from the supervising ethical committee of the Nobel Medical College Teaching Hospital, Biratnagar, Nepal. Written consents were taken from the subjects for the recruitment in the study. Results The present study involved 100 subjects of equal males and females subjects of age groups 17-45 years from Madheshis community of Nepal. The table 1, table 2, table 3 below shows the values obtained for different parameters for males and females. The mean value of nasal height for male and female is 52.59±1.89 and 50.27±2.16 mm and the nasal width for male and female is 37.64±1.72mm and 35.42±2.04mm and the value of mean nasal index for both the sexes are 71.59±2.31and 70.58±3.04 respectively. The dominant type of the nasal morphology in both the sexes are the mesorrhine type and the leptorrhine type as well. Conclusion The human nose is a dominant feature in facial region which differs in anatomy and morphology among racial groups and of the most characteristic differences during the analysis of ethnic and racial differences. The dominant type of the nasal index is the mesorrhine type in both the male and female of the Madheshis community. Hence the data obtained here will be useful for the differentiation of different ethnic groups of Nepal as well as in the field of forensic science and rhinoplastic surgery.
Keywords: Nasal Index; Mesorrhine; Dimorphism; Madheshis community